Critical Sites of Inclusion in India's Higher Education - Sengupta, Papia (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This book acquaints the reader to the often invisible-ized practices and policies under the rhetoric of 'inclusion', through theoretical and empirical analysis. It emphasizes on the complexities of education policies in a multicultural state by identifying the challenges to the idea of 'inclusion' illuminated through judicial interventions, policy-frameworks and everyday experiences of individuals. Higher education is imperative to empowerment in socially stratified societies marred with deep inequalities like India and many other multicultural countries. Disputes over inclusion remains a critical feature in Indian higher education sector, as it is viewed as facilitating access to economic opportunities and providing vertical mobility for individuals belonging to marginalized communities. Higher education empowers, and expands individual horizons of thought and ideas of freedom, dignity, equality, enabling individuals to participate actively in the political-sociological discourses in democratic polity. Therefore, policy makers, political theorists and educationists have been examining the question of inclusion and education as public-good. Contemporary India has witnessed an unprecedented attack on academic freedom, free exchange of ideas and expressions, challenging the very idea of inclusion and inclusiveness.
Introduction -- Chapter 1 Negotiating Inclusion: Minority institutions and constitutional-legal dimensions in India -- Chapter 2 From exclusion to inclusion-the case of public madarsa education system -- Chapter 3 Language Conundrum: English language and exclusivity in Indian higher education -- Chapter 4 Invisible voices: the case of endangered languages communities -- Chapter 5 Inclusive education: Analysing the Rights of Persons with Disabilities Act 2016 -- Chapter 6 Institutional barriers as hindrance to inclusion of women as members of academic community -- Chapter 7 Higher education and the question of inclusivity for LGBTQIA+ community -- Chapter 8 Interrogating neoliberal rationality and exclusivity of higher education -- Chapter 9 More technology-less access? Decoding ICT compliance in higher education -- Prologue: Placing 'inclusion' in the National Education Policy 2020.
Keywords: Education, Higher; Education and state; Identity politics; Higher Education; Education Policy; Identity Politics